2021
DOI: 10.1136/bmjopen-2020-043960
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to shared decision-making with women of reproductive age affected by a chronic inflammatory disease: a mixed-methods needs assessment of dermatologists and rheumatologists

Abstract: ObjectivesThe main study objective was to identify challenges and barriers experienced by dermatologists and rheumatologists when engaging women of reproductive age in shared decision-making (SDM) related to treatment and management of chronic inflammatory disease (CID) before, during and after pregnancy.DesignA mixed-methods study was conducted, employing (1) semistructured interviews, (2) an online survey and (3) triangulation of findings.Participants524 dermatologists and rheumatologists entered the study; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Nonetheless, shared decision-making between rheumatologists, patients and other healthcare providers can help optimize sex and gender-based priorities, leading to more efficient delivery of healthcare services. 21,22 Recently, there has been widespread discussion about the experiences of lesbian, gay, bisexual, transgender and queer (LGBTQ+) individuals in the healthcare system, the implicit and explicit biases many face, and difficulties in accessing necessary medical services. Educational materials often have biased representations of LGBTQ+ patients, which may contribute to social stigma.…”
Section: Disparities By Social Roles and Factorsmentioning
confidence: 99%
“…Nonetheless, shared decision-making between rheumatologists, patients and other healthcare providers can help optimize sex and gender-based priorities, leading to more efficient delivery of healthcare services. 21,22 Recently, there has been widespread discussion about the experiences of lesbian, gay, bisexual, transgender and queer (LGBTQ+) individuals in the healthcare system, the implicit and explicit biases many face, and difficulties in accessing necessary medical services. Educational materials often have biased representations of LGBTQ+ patients, which may contribute to social stigma.…”
Section: Disparities By Social Roles and Factorsmentioning
confidence: 99%
“…This has improved outcomes, including disease remission and prevention of disability. However, the range of medications used and their relative novelty can cause significant concern for women, their partners and healthcare practitioners with regard to safety during pregnancy and breast feeding 4. This may result in unnecessary and potentially harmful cessation of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant number of women will still experience active disease or increased disease activity. Flares in disease activity may be exacerbated by cessation of treatment often due to perceived safety concerns 4…”
Section: Introductionmentioning
confidence: 99%
“…Shared decision-making depends on clinicians having an in-depth understanding of the treatments to ensure informed counseling and consent as well as minimize decisional regret. However, a study reviewing the use of SDM in women of reproductive age found that dermatologists had “the perception that all biologics are strictly contraindicated during pregnancy,” demonstrating the gaps in knowledge.…”
mentioning
confidence: 99%